VaSe-MRP: Velocity-aware and stability-estimation–based multi-path routing protocol in flying ad hoc network. (November 2019) - Ma, Zhongyu; Guo, Qun; Ma, Ji; Zhang, Zhe; Ma, Hongfeng; Peng, Linru; Li, Ying
Flying ad hoc network is widely used in many military and civilian scenarios. Compared with mobile ad hoc network and vehicular ad hoc network, flying ad hoc network holds some special characteristics such as high mobility, long-distance communication, and sparse node-deployment, which cause an important challenge in the design of routing protocols. In this article, a velocity-aware and stability-estimation–based multi-path routing protocol is proposed for flying ad hoc network. The protocol is mainly composed of two important parts, which are the routing discovery mechanism and routing maintenance mechanism. In routing discovery process, the routing discovery request packet only can be forwarded by the reliable node, which is decided by the calculation of co-direction degree, then the routing overhead is reduced at some extent. Noticeably, the correlation of the survival duration between adjacent links is fully considered, which is very important to the path stability criteria. In routing maintenance progress, a path similarity and path remaining survival duration–based multi-path selection mechanism is proposed. The performance superiority of velocity-aware and stability-estimation–based multi-path routing protocol is also demonstrated by extensive simulations. The results show that velocity-aware and stability-estimation–based multi-path routing protocol is much better than other existing protocols in terms of network throughput, average delay of data transmission, routing overhead, and the convergence time of the routing discovery.